The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21911/aai.5033
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in the Diagnosis and Therapy of Allergic Rhinitis

Abstract: ÖZAllerjik rinit (AR) tüm yaş gruplarında görülen en sık ve kronik hastalıklardan biridir. Allerjik rinit IgE-aracılı nazal havayolunun allerjik enflamasyounu olup hapşırık, gözde kaşıntı-sulanma, burun mukozasının şişlik ve enflamasyonu ile kendini gösterir. Küresel sağlık problemi ve çocukluktan erişkinliğe kadar birçok kişiyi etkileyen ağır bir hastalıktır. Dünyada çocukluk çağı AR prevalansı %0.8 -45 arasında değişmektedir. Türkiye' de değişik bölgelerde sıklığı %2.9-44 olarak bildirilmektedir. Derlememizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Allergic rhinitis is classified as the seasonal/ intermittent type in which the symptoms develop in the pollen season and last no more than four days a week or less than four weeks in total, and the persistent/perennial type in which the symptoms occur year-round and last more than four days a week or more than four weeks (4). Moreover, based on the severity of the symptoms, it is classified as the mild type in which both sleeping and daily school and working activities are regular and the severe type in which both sleeping and daily school and working activities are disturbed (4,12). Our study cases generally were of the mild, intermittent type having no allergic rhinitis-related sleeping disorders with regular school and work activities.…”
Section: Discussionmentioning
confidence: 88%
“…Allergic rhinitis is classified as the seasonal/ intermittent type in which the symptoms develop in the pollen season and last no more than four days a week or less than four weeks in total, and the persistent/perennial type in which the symptoms occur year-round and last more than four days a week or more than four weeks (4). Moreover, based on the severity of the symptoms, it is classified as the mild type in which both sleeping and daily school and working activities are regular and the severe type in which both sleeping and daily school and working activities are disturbed (4,12). Our study cases generally were of the mild, intermittent type having no allergic rhinitis-related sleeping disorders with regular school and work activities.…”
Section: Discussionmentioning
confidence: 88%
“…In order to analyze the effects of NCS on the hypothalamic-pituitary-adrenal axis, 2-4 weeks of kinemometry was performed for their short-term effects, and 12 months of stadiometry was employed for their long-term effects ( 419 , 441 , 445 , 446 ). Although some studies have shown that beclomethasone dipropionate ( 447 ) and fluticasone furoate ( 445 ) sprays lead to growth suppression, mometasone furoate spray does not have any adverse effects on growth rate ( 448 ). However, some studies showed that beclometasone dipropionate nasal aerosol did not have any negative effects on the hypothalamic-pituitary-adrenal axis ( 449 ).…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%